“AND THEN I SMILED”: RECENT POSTCOLONIAL FICTION AND THE WAR ON TERROR - Silvia Albertazzi (Le Simplegadi, 2016)
The aim of this essay is to compare the reactions to the 2001 attack to the Twin Towers as they are related and reflected upon in Western and non- Western fiction. We start from the analysis of a novel by a Pakistani author, Mohsin Hamid, The Reluctant Fundamentalist. Then, we compare the genesis of a terrorist, as it is depicted by the American author John Updike in Terrorist, and the creation of a terrorist by the media, which is the main subject of The Unknown Terrorist by the Australian 2014 Man Booker Prize Winner Richard Flanagan.